Tourism development opportunities at the community level: a case study in lower Kinabatangan, Sabah, Malaysia - Chan, Jennifer Kim Lian (Universiti Malaysia Sabah, 1999)
Tourism development brings benefits of creating employment and thus generating income, providing econom1ic rationale for nature conservation, contributing to cultural preservation, and assisting community development. In recent years, there was an ongoing, unsustainable usage of natural resources in Lower Kinabatangan that caused the depletion of wildlife and resulted in a lose lose situation for the management of natural resources and the local people. Therefore, it is crucial to develop new tourism products to sustain tourism development for this community. This paper uses Bilit, situated in Lower Kinabatangan, as a case study of nature tourism development at the community level. The author was commissioned to conduct a study on the tourism potential of Bilit , which could be developed to create employment opportunities and to promote nature conservation efforts. This case study outlines the tourism development opportunities based upon the natural resources available. Discussion of partnership linkages between conservation and local participation has been highlighted in this case study. Findings of this study indicate that tourism opportunities exist in the historical and cultural attractions that could benefit villagers through employment and income generation. Historical attractions include the British Administration Office, the Government Rest House and the Clerk House which were built in 1790. In addition, the unique. Orang Sungai culture is an attraction that reflects Bilit's cultural character particularly its distinctive cultural patterns and traditions including the wedding ceremony, traditional dances and local handicrafts. This study concludes that new tourism products i.e. historical and cultural attractions in Bilit are tourism opportunities that can be successfully developed at the community level. This serves to upgrade the socio-economic status while promoting both the conservation of natural resources and the which are significant to Bilit culture at the community level. For the industry, it complements wildlife attraction through carrying capacity and cultural preservation of Orang Sungai.